1996
DOI: 10.1016/s0016-5085(96)70037-9
|View full text |Cite
|
Sign up to set email alerts
|

Low salt intake down-regulates the guanylin signaling pathway in rat distal colon

Abstract: Background & Aims-Guanylin, an endogenous gastrointestinal peptide, causes the translocation of NaCl from interstitial fluid to the intestinal lumen. The aim of this study was to examine whether changes in dietary salt intake lead to compensatory changes in expression of the guanylin signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Although the physiological function of the guanylin peptides in teleosts is still uncertain, studies have shown that they may play a role in long-term salinity adaptation. Indeed, GN and UGN mRNA expression increase following a 24-h transfer from freshwater (FW) to SW by at least twofold in the Japanese eel (Anguilla japonica) (12,39,67), a pattern also observed in the rat after salt loading of intestinal tissues (8,40,45). In mammalian tissues, GN and UGN either increase the secretory short-circuit current (I sc ) of the intestine or reverse an absorptive I sc , while in teleosts, these peptides have no effect on the anterior intestine of the Japanese eel, but do reverse the I sc of the mid and posterior intestine, resulting in a net serosa-to-mucosa flux of, presumably, Cl Ϫ ions (38,54,68).…”
mentioning
confidence: 81%
“…Although the physiological function of the guanylin peptides in teleosts is still uncertain, studies have shown that they may play a role in long-term salinity adaptation. Indeed, GN and UGN mRNA expression increase following a 24-h transfer from freshwater (FW) to SW by at least twofold in the Japanese eel (Anguilla japonica) (12,39,67), a pattern also observed in the rat after salt loading of intestinal tissues (8,40,45). In mammalian tissues, GN and UGN either increase the secretory short-circuit current (I sc ) of the intestine or reverse an absorptive I sc , while in teleosts, these peptides have no effect on the anterior intestine of the Japanese eel, but do reverse the I sc of the mid and posterior intestine, resulting in a net serosa-to-mucosa flux of, presumably, Cl Ϫ ions (38,54,68).…”
mentioning
confidence: 81%
“…In the rat distal colon, high sodium diet did not change the expression of guanylin, but low sodium diet down-regulates its expression (44). In the mouse kidney, however, high oral salt intake increases the expression of uroguanylin (45).…”
Section: A Novel Guanylin Family In Eel-mentioning
confidence: 92%
“…In mammals, guanylin and uroguanylin cause increased HCO 3 Ϫ secretion into the intestinal lumen; accordingly, it has been suggested that uroguanylin might play a role in defending the pH of the intestine, as acidic chyme enters from the stomach (11). Conversely, guanylin transcription and secretion are increased in rat intestinal tissues when perfused with high salt concentrations and decreased with low salt intake (7,29,32). Conceivably, in seawater teleosts, uroguanylin plays a more prominent role in digestion, and guanylin takes a more active part in osmoregulatory processes.…”
Section: Significance and Perspectivesmentioning
confidence: 99%